The triglyceride-glucose index as a novel marker associated with sarcopenia in non-diabetic patients on maintenance hemodialysis. Issue 1 (31st December 2022) - Chen, Ruoxin; Zhang, Liuping; Zhang, Mengyan; Wang, Ying; Liu, Dan; Li, Zuolin; Zhang, Xiaoliang; Jin, Hui; Liu, Bicheng; Liu, Hong
Abstract: Objective: Sarcopenia is a common complication in patients with end-stage kidney disease. Insulin resistance is present in non-diabetic patients undergoing maintenance hemodialysis (MHD) and is an important factor leading to sarcopenia. The triglyceride–glucose (TyG) index, a reliable indicator for evaluating insulin resistance, is widely used in clinical practice. The present study investigated the association between the TyG index and sarcopenia in non-diabetic patients undergoing MHD. Methods: Relevant clinical data of non-diabetic patients undergoing MHD at our center were collected. The TyG index was calculated using the following formula: ln(fasting triglycerides(mg/dL)×fasting blood glucose(mg/dL)/2). Multivariate logistic regression analyses were used to evaluate the associations. The receiver-operating characteristic curve was used to analyze the predictive value of the TyG index in sarcopenia. Results: Of the 142 patients undergoing MHD who were included, 75 (52.82%) were men, the mean age was 54.05 ± 13.97 years, and 40 (28.17%) patients satisfied the diagnostic criteria for sarcopenia. The TyG index of participants with sarcopenia was higher compared with those without sarcopenia (8.83 ± 0.45 vs. 8.49 ± 0.50, p < 0.001). The prevalence of sarcopenia increased with increasing TyG index tertile (T1, 8.51%; T2, 31.91%; T3, 43.75%; p = 0.001). Logistic regression analysis indicated that the TyG index was an independent risk factor for sarcopenia (odds ratio, 4.21 [95% confidence interval, 1.85–9.59], p = 0.001). Conclusion: A higher TyG index was associated with an increased risk of sarcopenia in non-diabetic patients undergoing MHD; it may be used as a novel marker to reflect the presence of sarcopenia.